If it's not what You are looking for type in the equation solver your own equation and let us solve it.
31=7(-5n-7)-4(2-6n)
We simplify the equation to the form, which is simple to understand
31=7(-5n-7)-4(2-6n)
Reorder the terms in parentheses
31=+(-35n-49)-4*(2-6n)
Remove unnecessary parentheses
+31=-35n-49-4+*(+2-6n+)
Reorder the terms in parentheses
31=-35n-49+(-8+24n)
Remove unnecessary parentheses
+31=-35n-49-8+24n
We move all terms containing n to the left and all other terms to the right.
+35n-24n=-49-8-31
We simplify left and right side of the equation.
+11n=-88
We divide both sides of the equation by 11 to get n.
n=-8
| 3x^2-6x-(2-k)=0 | | .03y+.09(50000-y)=2490 | | (2x+5)+(4x-11)= | | -6(1+2x)=90 | | 1b+4b=8b-b | | 3t^2+14t+4=0 | | 2y-(7-5y)-21=0 | | 4-M=6 | | 400+2+3=1050 | | -0.441+x/2.2=0.922 | | 35+d=17 | | 50.00+3.75b=800 | | 50.00+3.75b=400 | | -16=x+47 | | -3/7+2k=-86/21 | | 32+d=17 | | 50.00+3.75=400 | | -7652+185x=-12790 | | x-14=28 | | 40=20-2v | | (76+93+84+68+92+y)/6=80 | | -4-6x=-10 | | 50.00+3.75=0 | | 2/5x210 | | 6=v-5/3 | | 6x-3=5z-5 | | 7x-4x=132 | | -7652+185x=12790 | | x^4-9x^2-3=0 | | 11.9x=3.57 | | 3-x=12+x | | -31/9=2r |